Pengaruh Model Pembelajaran Role Reversal Questions Terhadap Hasil Belajar Sejarah Kebudayaan Islam Siswa Mtsn 10 Ngawi - Ihwan Mahmudi; Chevira Yasin Putri Indriyanti; Aina Nur Hilmy Harahap (Departement of Mathematics Education, 2024)
The history of Islamic culture is one of the Islamic religious education lessons taught to introduce the history of Islamic culture to students. The role reversal questions learning model is an active learning model that emphasizes question and answer with the exchange of roles between teachers and students. The application of the Role Reversal Questions learning model during the learning process of Islamic Cultural History is expected to be able to improve learning outcomes and student activity during learning takes place. This research was conducted to know the effect of the Role Reversal Questions learning model on the learning outcomes of Islamic Cultural History subjects at MTsN 10 Ngawi. The research method used is a quantitative experimental approach with the True Experimental research design and data acquisition is carried out through tests and documentation, which are analyzed by Descriptive Analysis. Based on the results of the Mann Whitney hypothesis test that was submitted and managed with the help of the SPSS 16 application, it is known that the post-test score for the Experiment class obtained an average of 84.29 and the post-test value for the Control class received a value of 70.54, and from the explanation of the Mann Whitney test results of 0.000 is smaller than 0.05, which means that Ho is rejected and Ha is accepted. this indicates that there is an influence between the Role Reversal Questions learning model on the learning outcomes of Islamic Cultural History students at MTsN 10 Ngawi.